Faktor Risiko Komorbid HIV dan Tuberkulosis di Rumah Sakit Umum Daerah Merauke - Maria Anggi Sylvani; Yvonne Suzy Handajani; Lusia Gani (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2019)
Background: Tuberculosis is a disease that has a close relationship with HIV. HIV-TB infections interact directly (bidirectional) and synergisticly. Risk factors such as sociodemography, lifestyle, CD4 levels, Hb levels and consumption of IPT can affect the occurrence of HIV-TB co-infection.Objective: To obtain an overview of the prevalence of TB in HIV patients and their determinant factors in Rumah Sakit Umum Daerah Merauke.Methods: This study was conducted on HIV patients who came to the Pokja of Rumah Sakit Umum Daerah Merauke (n = 107). This was a cross sectional research with interview forms and medical records as the instruments. Univariate, bivariate, and multivariate analyzes were performed using the SPSS data processing program version 22 with Chi Square statistical tests at a 95% confidence level. Results: Bivariate analysis results in this study showed occupational groups (p= 0.028), education groups (p = 0.034), ethnicity / race (p = 0.042), location of residence (p = 0.033), smoking habits (p = 0.012) , physical activity (p = 0.039), CD4 level (p = 0,000), Hb level (p = 0,000), Isoniazid Preventive Therapy (IPT) (p = 0.016) were associated with HIV-TB co-infection.Conclusion: The risk factors, such as job, education, ethnic / racial risk factors, location of residence, smoking habits, physical activity, CD4 levels, Hb levels and consumption of IPT were influencing the incidence of TB co-infection in HIV patients.